The Tuktu and Nogak Project: Inuit Knowledge about Caribou and Calving Areas in the Bathurst Inlet Region - Thorpe, Natasha L. (ARCTIC, 1997)
. Traditional ecological knowledge is central to Inuit culture in general, and to the sustainable management of lands, resources, and wildlife in particular. Since lifestyles in the Bathurst Inlet region are changing at the same time that elders are passing on and taking their wisdom with them, efforts to document this knowledge are critical. Mineral exploration and the potential for mine development, along with other land use issues, further compound this imperative. For these reasons, a two-year study entitled The Tuktu (caribou) and Nogak (calves) Project ("the project") was initiated in February 1997, with the primary goal of documenting and communicating Inuit knowledge about caribou and calving areas in the Bathurst Inlet region. .